2022
DOI: 10.1183/23120541.00565-2021
|View full text |Cite
|
Sign up to set email alerts
|

Hypnosis for the management of COPD-related anxiety and dyspnoea in pulmonary rehabilitation: rationale and design for a cluster-randomised, active-control trial (HYPNOBPCO_2)

Abstract: Complementary psychological care is recommended for COPD, as it significantly reduces anxiety, and boosts the pulmonary rehabilitation efficacy. In a precedent trial (HYPNOBPCO_1, ISRCTN10029862), administering a single hypnosis session was linked to reduced anxiety and improved breathing mechanics in intermediate and advanced COPD patients. However, whether hypnosis could improve self-management of anxiety and dyspnea in COPD during pulmonary rehabilitation is yet to be investigated.This is the protocol for H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Currently, we observe a growing number of studies addressing the issue of the use of non-pharmacological methods in the treatment of COPD patients affected by anxiety. The evaluated interventions included: relaxation ( 79 , 80 ), hypnosis ( 81 ), cognitive behavioral therapy ( 82 ), and mindfulness ( 83 ). One study investigated also breathing techniques and found out them beneficial in managing anxiety ( 84 ).…”
Section: Anxiety Managementmentioning
confidence: 99%
“…Currently, we observe a growing number of studies addressing the issue of the use of non-pharmacological methods in the treatment of COPD patients affected by anxiety. The evaluated interventions included: relaxation ( 79 , 80 ), hypnosis ( 81 ), cognitive behavioral therapy ( 82 ), and mindfulness ( 83 ). One study investigated also breathing techniques and found out them beneficial in managing anxiety ( 84 ).…”
Section: Anxiety Managementmentioning
confidence: 99%
“…Interestingly, as of 2022, many new trials assessing the impact of hypnotic interventions on depression and anxiety symptoms are currently in progress, which shows that the technique continues to accrue interest in the medical community (e.g., Anlló et al, 2021a ; Grégoire et al, 2022 ; Fernandes et al, ongoing NCT04010825). In particular, at least two of these ongoing trials are targeting the use of hypnosis specifically for the psychological and emotional correlates of COPD ( Anlló et al, 2021b ; Fernandes et al, ongoing NCT04010825).…”
Section: Hypnosis and The Complementary Management Of Mood And Respir...mentioning
confidence: 99%